Dynamic Data Assimilation Beating the Uncertainties - Harkut, Dinesh G. (IntechOpen, 2020)
Data assimilation is a process of fusing data with a model for the singular purpose of estimating unknown variables. It can be used, for example, to predict the evolution of the atmosphere at a given point and time. This book examines data assimilation methods including Kalman filtering, artificial intelligence, neural networks, machine learning, and cognitive computing.